Multimedia as Digital Literacy in Culinary Arts Vocational Learning - Kandriasari, Annis; Yulianti, Yeni; Riska, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Learning media plays an important role in attracting students attention to understand the material. The results of observations of D3 Tata Boga 2017 students showed that only 18 out of 39 students reached the minimum completion criteria (78%) on napkin folding material, with learning resources limited to modules and jobsheets. One of the learning media through computers is using adobe flash player. The use of adobe flash player has not been utilized by the Culinary Study Program for student learning resources on napkin folding material. Based on this fact, learning to make napkin folds requires a stimulus from the lecturer, namely through the development of learning media. This study aims to develop and test the feasibility of interactive multimedia as digital literacy on napkin folding material. This study used R&D with a 4D development model (Define, Design, Develop, and Disseminate). The data analysis technique used the Content Validity Ratio (CVR) method. The interactive multimedia-based program uses Adobe Animate 2019 and Adobe Premiere Pro CC 2019. The interactive multimedia developed consists of several features including an introductory menu, theory, video tutorials, and knowledge test questions as the final score. The results show user validation of 0.41 and are included in the appropriate CVR criteria. Based on the results of the validation of the material expert, the feasibility was obtained at 94.6% and 85.7% for the high feasibility aspect criteria. The results of the media expert validation obtained a feasibility value of 86.4% and 81.8% for the high feasibility aspect criteria. The field group trial consisting of 30 culinary program students obtained results of 84.38% and were included in the feasibility criteria. It is concluded that interactive multimedia as digital literacy is declared “suitable” as a learning resource in the Food and Beverage Service course.